A Genome Assembly of the Barley 'Transformation Reference' Cultivar Golden Promise. Issue 6 (1st June 2020) - Schreiber, Miriam; Mascher, Martin; Wright, Jonathan; Padmarasu, Sudharasan; Himmelbach, Axel; Heavens, Darren; Milne, Linda; Clavijo, Bernardo J; Stein, Nils; Waugh, Robbie
Abstract: Barley ( Hordeum vulgare ) is one of the most important crops worldwide and is also considered a research model for the large-genome small grain temperate cereals. Despite genomic resources improving all the time, they are limited for the cv . Golden Promise, the most efficient genotype for genetic transformation. We have developed a barley cv . Golden Promise reference assembly integrating Illumina paired-end reads, long mate-pair reads, Dovetail Chicago in vitro proximity ligation libraries and chromosome conformation capture sequencing (Hi-C) libraries into a contiguous reference assembly. The assembled genome of 7 chromosomes and 4.13Gb in size, has a super-scaffold N50 after Chicago libraries of 4.14Mb and contains only 2.2% gaps. Using BUSCO (benchmarking universal single copy orthologous genes) as evaluation the genome assembly contains 95.2% of complete and single copy genes from the plant database. A high-quality Golden Promise reference assembly will be useful and utilized by the whole barley research community but will prove particularly useful for CRISPR-Cas9 experiments.